Nationalism in modern Europe politics, identity and belonging since the French Revolution - Hastings, Derek (Derek Keith) (Bloomsbury Academic, 2023)
"Nationalism has been, without question, one of the most potent political and cultural forces within Europe since the late-18th century. Placing particular emphasis on transnational and comparative links, Nationalism in Modern Europe provides a clear and accessible history of the development of nationalism in Europe from the French Revolution to the present. The book situates nationalist ideas and movements in Europe firmly within the context of other signifiers of identity and belonging--such as religion, race, and gender--while also providing comprehensive geographic coverage across Europe. It incorporates recent historiographical trends and debates as part of the discussion and includes 30 images, 10 maps and a range of primary source excerpts for classroom use. It is an essential volume for all students of the history of nationalism in modern Europe and a useful text for anyone seeking to know more about modern European history in general."--Provided by publisher.